Analisis Metode RGEC untuk Penilaian Kinerja pada PT Bank Mandiri (Persero) Tbk - Fitria Asmawati; Lis Setyowati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research aims to analysis the soundness level of banks using the RGEC method at PT Bank Mandiri (Persero) Tbk in 2018-2021. The data studied is in the form of financial statements of PT Bank Mandiri (Persero) Tbk for 2018-2021. The data collection technique used is the documentation technique. The data analysis technique used is a qualitative descriptive analysis technique using the RGEC method. The results of this research show that Bank Mandiri for 2018-2021 is viewed from the aspect of risk profile with two ratios, namely the ratio of Non-Performing Loans for banks in a healthy condition and the ratio of Loan to Deposit Ratio for banks in a fairly healthy condition. Aspects of Good Corporate Governance get the title of very healthy. Earnings aspect with two ratios, namely the ratio of the bank's Return on Assets in a very healthy condition and the ratio of the bank's Net Interest Margin in a healthy condition. Aspects of Capital with the ratio of Capital Adequacy Ratio of the bank is in very healthy condition.